Rule of Law, Happiness, and Human Health: Mechanisms and Effects - Lin, Ling; Tao, Ran; Zafar, Quratulain; Mahmood, Chaudhry Kashif (Frontiers in Public Health, 2022)
Human health is an important concern that gradually exists in sustainable development goals. The key aim of this study is to examine the impacts of the rule of law on happiness and health using a time series data of China over the data period 1998–2020. The empirical analysis utilizes the autoregressive distributed lag (ARDL) method to find out the short and long-run effects. Findings reveal that the rule of law stimulates happiness and human health in the long-run. More internet and GDP enhance happiness and human health in the long-run. The results also showed that health expenditure and education could not boost happiness and health in the long run, but unemployment's negative effect on health. Policymakers may use our empirical results to determine applicable policies to increase human health across China provinces.